Family Economic Security - Acheson, Ann (Maine Policy Review, 2009)
Research shows that family economic insecurity when children are very young can have lifelong effects. Ann Acheson gives an overview of patterns of poverty and family economic insecurity in Maine, including the marked regional differences in poverty, income, and employment in the state. She describes some of the key benefits and programs to help support lower-income families and examines current policies and policy recommendations for addressing poverty and economic insecurity. Acheson notes that while Maine has been progressive in many of its policies that support family economic security, states can’t do it all, since much of the program and benefits funding, along with policies and eligibility requirements, are from federal sources.